LINE BALANCING PERAKITAN CABIN MENGGUNAKAN METODE RANKED POSITIONAL WEIGHT (RPW) DAN BAHASA PEMROGRAMAN MATLAB - Dwiparaswati, Windy (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2024)
The Indonesian automotive industry has become an important pillar in the country's manufacturing sector. As production capacity increases, problems will also increase, including disparities in the level of efficiency and productivity of each sub-sector of the manufacturing industry in Indonesia. This occurs due to not having a good process path, such as the uneven distribution of work tasks / machines in the work process so that it is possible to harm the company, so that a solution is needed to increase the efficiency of the production line. This study aims to improve the efficiency of the SL type cabin assembly line production by implementing the Ranked Positional Weight (RPW) method. The research stages include data collection, data analysis, data processing and evaluation. Based on the simulation results, SL type cabin using the Ranked Positional Weight (RPW) method has increased track efficiency by 4.69% from the initial condition, the track efficiency of 75.02% increased to 79.71%. The increased efficiency of the production line can also reduce idle time in the SL type cabin assembly. Based on the calculation results, it can be concluded that by implementing the Ranked Positional Weight (RPW) method can reduce 1 production operator for the SL type cabin assembly so that it can increase the efficiency of the SL type cabin assembly line by reducing idle time.